М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
genatbukin
genatbukin
26.06.2021 21:40 •  Алгебра

( Решите уравнение

а) x2-2x/x-1 - 2x-1/1-x = 3
б) x2-2x+1/x-3 + x+1/3-x = 4
в) 2/x-4 + 4/x2-4x = 0,625​

👇
Ответ:
pro100miss
pro100miss
26.06.2021

a)\ \ \dfrac{x^2-2x}{x-1}-\dfrac{2x-1}{1-x}=3\ \ ,\ \ \ \ ODZ:\ x\ne 1\ ,\\\\\\\dfrac{x^2-2x}{x-1}+\dfrac{2x-1}{x-1}=3\ \ ,\ \ \ \dfrac{x^2-2x+2x-1}{x-1}=3\ \ ,\ \ \dfrac{x^2-1}{x-1}=3\ \ ,\\\\\\x^2-1=3(x-1)\ ,\ \ \ x^2-1=3x-3\ \ ,\ \ \ x^2-3x+2=0\ \ \ ,\\\\x_1=1\notin ODZ\ \ ,\ x_2=2\ \ (teorema\ Vieta)\\\\Otvet:\ \ x=2\ .

b)\ \ \dfrac{x^2-2x+1}{x-3}+\dfrac{x+1}{3-x}=4\ \ ,\ \ \ \ ODZ:\ x\ne 3\ ,\\\\\\\dfrac{x^2+2x+1}{x-3}-\dfrac{x+1}{x-3}=4\ \ ,\ \ \ \dfrac{x^2+2x+1-x-1}{x-3}=4\ \ ,\ \ \dfrac{x^2+x}{x-3}=4\ ,\\\\\\x^2+x=4(x-3)\ \ ,\ \ \ x^2-3x+12=0\ \ ,\ \ D=-39

c)\ \ \dfrac{2}{x-4}+\dfrac{4}{x^2-4x}=0,625\ \ ,\ \ \ \ ODZ:\ x\ne 0\ ,\ x\ne 4\ ,\\\\\\\dfrac{2}{x-4}+\dfrac{4}{x\, (x-4)}=\dfrac{5}{8}\ \ ,\ \ \ \dfrac{2x+4}{x\, (x-4)}=\dfrac{5}{8}\ \ ,\ \ \ 16x+32=5x(x-4)\ \ ,\\\\\\16x+32=5x^2-20x\ \ ,\ \ \ 5x^2-36x-32=0\ \ ,\ \ D/4=484=22^2\ ,\\\\x_1=\dfrac{6-22}{5}=-3,2\ \ \ ,\ \ \ x_2=\dfrac{6+22}{5}=5,6

4,5(22 оценок)
Открыть все ответы
Ответ:
mivaniuk
mivaniuk
26.06.2021
a)
log_{0.5} ( x^{2} -3x)=-2

ОДЗ:
x^2-3x\ \textgreater \ 0

x(x-3)\ \textgreater \ 0
 
    +              -                +
---------(0)----------(3)-------------
///////////                  ////////////////

x ∈ (- ∞ ;0) ∪ (3;+ ∞ )

log_{0.5} ( x^{2} -3x)= log_{0.5} 0.5^{-2}

log_{0.5} ( x^{2} -3x)= log_{0.5} 4

x^{2} -3x= 4

x^{2} -3x-4=0

D=(-3)^2-4*1*(-4)=9+16=25=5^2

x_1= \frac{3+5}{2}=4

x_2= \frac{3-5}{2}=-1

ответ: -1; 4

b)
log^2_{2} (x-2)- log_{2} (x-2)=2

ОДЗ:

x-2\ \textgreater \ 0

x\ \textgreater \ 2

log^2_{2} (x-2)- log_{2} (x-2)-2=0

Замена:  log_{2} (x-2)=t

t^2-t-2=0

D=(-1)^2-4*1*(2)=1+8=9

t_1= \frac{1+3}{2}=2

t_2= \frac{1-3}{2}=-1

log_{2} (x-2)=2   или   log_{2} (x-2)=-1

x-2=4       или       x-2=0.5

x=6         или        x=2.5

ответ:  2,5;  6
 
c)
log_{3} ( x^{2} +2x)\ \textless \ 1

ОДЗ:
x^{2} +2x\ \textgreater \ 0

x(x+2)\ \textgreater \ 0
 
    +              -                +
---------(-2)----------(0)-------------
///////////                  ////////////////

x ∈ (- ∞ ;-2) ∪ (0;+ ∞ )

log_{3} ( x^{2} +2x)\ \textless \ log_{3}3

x^{2} +2x\ \textless \ 3

x^{2} +2x-3\ \textless \ 0

D=2^2-4*1*(-3)=4+12=16

x_1= \frac{-2+4}{2}=1

x_2= \frac{-2-4}{2}=-3

     +                -                  +
----------(-3)-----------(1)--------------
               /////////////////

С учётом ОДЗ получаем

ответ: (-3;-2) ∪ (0;1)

d)
log_{ \frac{1}{3} } (0.1x-5.2)\ \textgreater \ 2

ОДЗ:
0.1x-5.2\ \textgreater \ 0

0.1x\ \textgreater \ 5.2

x\ \textgreater \ 52

log_{ \frac{1}{3} } (0.1x-5.2)\ \textgreater \ log_{ \frac{1}{3} } \frac{1}9}

0.1x-5.2\ \textless \ \frac{1}9}

0.1x\ \textless \ \frac{1}9} +5 \frac{1}{5}

0.1x\ \textless \ \frac{5}{45} +5 \frac{9}{45}

0.1x\ \textless \ 5 \frac{14}{45}

\frac{1}{10} x\ \textless \ \frac{239}{45}

x\ \textless \ \frac{239}{45} *10

x\ \textless \ 53 \frac{1}{9}

С учётом ОДЗ получаем

ответ: (52;53 \frac{1}{9})
4,6(50 оценок)
Ответ:
Jannalizahappy
Jannalizahappy
26.06.2021

1)       ac2-ad+c3-cd-bc2+bd=  = (ac2 – ad) + (c3 –

bc2) + (bd – cd) = a·(c2 – d) + c2·(c – b) + d·(b     – c) = a·(c2 – d) +

c2·(c – b) – d·(c – b) = a·(c2 – d) + c2·(c – b) – d·(c – b) = a·(c2 –

d) + (c – b)·(c2 – d) = (c2 – d)·(a + c – b)

2)  mx2+my2-nx2-ny2+n-m= x2 ( m - n ) + y2 ( m - n ) - ( m - n ) = ( m-n ) (x2 + y2 - 1 )  

3)   am2+cm2-an+an2-cn+cn2= m2 (a + c ) + n2 ( a + c ) - n ( a + c ) = ( a+ c) ( m2 + n2 - n) 

4)   xy2-ny2-mx+mn+m2x-m2n= y2 ( x - n ) + m2 ( x - n) - m ( x - n ) = ( x-n) ( y2 + m2 - m ) 

5)   a2b+a+ab2+b+2ab+2=ab ( a + b + 2 )   + ( a+ b+ 2 ) = 2 ( a+ b + 2 ) 

6)   x2-xy+x-xy2+y3-y2=   x ( x –   y + 1) –   y 2 ( x –   y + 1)=( x –   y + 1)( x –   y 2 ).

4,4(4 оценок)
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ